2010
DOI: 10.1017/s1047951110000661
|View full text |Cite
|
Sign up to set email alerts
|

Novel regression equations of left ventricular dimensions in infants less than 1 year of age and premature neonates obtained from echocardiographic examination

Abstract: The regression equations reported in the previous studies cannot be applied to data obtained from infants. In addition, three different formulae, one for each group of infants by using height as an index can be usefully applied for practical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
1
18
2
Order By: Relevance
“…16 Nagasawa et al concluded length was an appropriate index for LVEDD in patients under age 1 year with only 32 patients less than 32 weeks gestation. 46 These prior studies did not utilize centile curves for LV dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nagasawa et al concluded length was an appropriate index for LVEDD in patients under age 1 year with only 32 patients less than 32 weeks gestation. 46 These prior studies did not utilize centile curves for LV dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…16 LVDd% of normal (LVDd%N) 24 was calculated in percent as estimated LVDd, where estimated LVDd (in mm)=0.495× BH (in cm)-5.43. 18 To seek an easier but accurate correction of LAV4CV, we performed linear regression between LAV4CV and BH, and obtained the estimated LAV4CV by BH. Subsequently, we calculated LAV4CV %N.…”
Section: Discussionmentioning
confidence: 99%
“…We used indomethacin during the acute phase after 18 h of age in ELBWIs who showed no tendency for the PDA to close, who had a large left-to-right shunt, and who fulfilled some of the following criteria: (1) LA enlargement indicated by an LA/Ao ratio >1.3; (2) peak LPA edv >15 cm/s; (3) retrograde flow of renal arteries; and (4) LV end-diastolic dimension (LVDd) >≈120% of the normal estimated value. 18 Physical and ultrasonographic measurements were performed as an integral part of the routine clinical practice for ELBWIs in the NICU. The latter included obtaining informed consent from the patient's parents.…”
mentioning
confidence: 99%
“…While echocardiography has long been used for assessments of the size of the heart in children, this study applied two-dimensional echocardiography to assess the development of left ventricular end-diastolic dimension (LVDd) and the rate of development by using height as an index in neonates during the late neonatal period and in infants with body heights less than 75 cm [1][2][3]. Linear relationship between height and LVDd were detectable, excluding neonates with physiological pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The following were the objectives of this study: (1) to show the changes in the flatness ratio in the shortaxis view, (2) to assess the transition of the endocardiac circumference length of the internal margin of the left ventricle in the short-axis view in physiological pulmonary hypertension, (3) to compare real LVDds and normal LVDds that were estimated by the formula previously reported, and (4) to reveal what the real LVDds imply at this age.…”
Section: Introductionmentioning
confidence: 99%